PENERAPAN AKUNTANSI PADA DESA WISATA NGLINGGO KABUPATEN KULON PROGO - Wulandari, Dwi; Widarno, Bambang; Suharno, Suharno (Universitas Slamet Riyadi, 2019)
The program for the development and utilization of resources and the potential of regional tourism are expected to contribute to economic development. In order for tourism development to run optimally, good fund management is needed by applying accounting that is in accordance with the standards, namely the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). This study aims to determine the application of accounting and help the preparation of financial statements in Nglinggo Tourism Village Kulon Progo Regency based on Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). This study uses qualitative research with a case study method. The data source used is secondary data. The data collection technique used is documentation and literature study. The data analysis technique uses descriptive analysis. The results of this study indicate that Nglinggo Tourism Village is a Tourism Village Management Agency engaged in services. Recording conducted by Nglinggo Tourism Village is manual and not computerized, which is used to determine the amount of profit and loss and the amount of salary costs and profit sharing costs so that it is still far from SAK ETAP. Based on this, the researchers sought to assist in the preparation of the financial report of Nglinggo Tourism Village in accordance with SAK ETAP, namely by preparing a system and accounting procedures based on the accounting cycle consisting of identifying stages, recording stages, classification stages, summarizing stages and reporting stages in the form of earnings reports loss and balance sheet. Based on the results of the financial statements that have been prepared, it shows that the income of Nglinggo Tourism Village is relatively large, where in 2017 the total income earned was Rp 281,819,000 with net income of Rp 65,608,792.